The role of improved physical aspect among Bus2a students - Yting, Cristilyn (2007)
This study aimed to assess the role of Bus2a course in the students' improved physical aspect and relate it with their self-confidence. The respondents of the study were students of the College of Business and Accountancy at La Salle University (LSU) second semester SY 2006-2007. The questionnaire used was adapted from Santos (1974, 2006) "Personality Development for for the Woman of Today" and Charm and Personality".
Keywords: Personality development